2016
DOI: 10.1177/0886260516672941
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Predictors of Bullying Victimization With Routine Activity and Social Bond Perspectives

Abstract: Bullying victimization in school settings is a serious problem in many countries including the United States. It has been associated with serious incidents of school violence as well as detrimental physical, psychological, emotional, and social consequences for its victims. Given its consequences, it is crucial to understand who is more likely to be targeted for bullying victimization. This study examines whether a number of important factors such as gender, physical and interactionist school security measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 54 publications
(140 reference statements)
3
17
0
Order By: Relevance
“…The study found that in-school adolescents who were bullied were significantly more likely to experience interpersonal violence. This result is congruent with previous studies conducted elsewhere [16,26,31]. These studies have shown that bullying victimization was associated with increased violent behavior in adolescents.…”
Section: Discussionsupporting
confidence: 93%
“…The study found that in-school adolescents who were bullied were significantly more likely to experience interpersonal violence. This result is congruent with previous studies conducted elsewhere [16,26,31]. These studies have shown that bullying victimization was associated with increased violent behavior in adolescents.…”
Section: Discussionsupporting
confidence: 93%
“…Existing scholarly evidence from sub-Saharan African countries shows that Ghana, Mozambique, Nigeria and Malawi have reported a high prevalence of bullying victimisation (i.e., 56% [ 11 ], 45.5% [ 3 ], 16.3% [ 12 ], and 44.5% [ 13 ]) respectively. Additionally, socio-demographic (e.g., sex, age, economic status: [ 3 , 12 18 ]) and behavioural characteristics (e.g., loneliness, physical fighting, sexual behaviours, substance use, truancy: [ 2 , 3 , 19 – 21 ]) have been identified as correlates of bullying victimisation. Specifically, bullying victimisation is inclined towards boys [ 22 , 23 ]; less prevalent with increasing age [ 22 , 24 , 25 ]; increaseswith loneliness [ 26 ]; high among those who have no friends [ 27 ]; high among thosw who always have negative feelings, such as worries, sadness, unhappiness, or hopelessness [ 28 ]; high among those with low self-esteem [ 29 ]; and those suicide ideation [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cohen and Felson's (1979) routine activity theory posits that crime is more likely when motivated offenders come into contact with suitable targets in the absence of capable guardians. For most youth, school attendance is a central routine activity and it is well established that schools vary in the presence of offenders, targets and guardians (Cecen-Celik and Keith, 2016;Popp, 2012;Popp and Peguero, 2011). Within schools, bullying is a prevalent and harmful form of peer victimization that consists of repeated and intentionally harmful behaviour perpetrated by a more powerful individual or group against a less powerful individual or group (Gini and Pozzoli, 2009;Olweus, 1993;Wang et al, 2009).…”
Section: Sros and School Safetymentioning
confidence: 99%
“…Although several studies have explored the relationship between SROs and other forms of guardianship on some forms of school-based victimization (Augustine et al, 2002;Peguero, 2009;Peguero et al, 2015;Popp, 2012;Wilcox et al, 2009), few studies have focused on the association between capable guardians and bullying (Cecen-Celik and Keith, 2016;Gerlinger and Wo, 2016;Popp, 2012;Robles-Pina and Denham, 2012). Using a composite measure of several school security practices, Cecen-Celik and Keith (2016) found no effect of physical security on bullying victimization (see also Burrow and Apel, 2008;Popp, 2012;Schreck et al, 2003).…”
Section: Capable Guardianship and Bullying Preventionmentioning
confidence: 99%
See 1 more Smart Citation